Optimization of medium for the production of β-cyclodextrin glucanotransferase using Central Composite Design (CCD) - Ibrahim, Hanan Moawia; Wan Yusoff, Wan Mokhtar; Abdul Hamid, Aidil; Md. Illias, Rosli; Hassan, Othman; Omar, Othman (Elsevier Limited, 2005)
Production of cyclodextrin glucanotransferase (CGTase) from Bacillus G 1, a new bacterial isolate was optimized in shake-flask cultures using statistical design approach. An efficient fermentation medium producing CGTase with high activity (54.9U/ml) was determined: A 2(5) Central Composite Design (CCD; half fraction) has been chosen to elucidate the combined effect of five process variables; tapioca starch, peptone, yeast extract, magnesium sulphate and potassium phosphate concentration. Concentrations of 4% tapioca starch, 2% peptone, 0.04% magnesium sulphate and 1 % sodium carbonate have been shown to be optimum for the production of CGTase.